Heterogeneity of Social Returns to Education Across Employees Education Levels in Indonesia - Ribut Nurul Tri Wahyuni; Retnaningsih Retnaningsih; Lia Yuliana (Faculty of Economics and Business Universitas Jenderal Soedirman, 2025)
This study estimates the heterogeneity of agglomeration externalities across employees' education levels in Indonesia. This study uses the 2020-2024 microdata and the Instrumental Variable (IV) Heckman model with the historical population density and the number of universities as IVs. The result indicates that social returns to education from the local high-skill labor market, which is a part of agglomeration externalities, are positively significant and higher for high- and medium-skilled employees than for low-skilled employees. This finding demonstrates the efficacy of public education investments, especially Indonesian government policy that can enhance the quantity and quality of university graduates, thereby promoting the transfer of knowledge to all employees and eventually reducing wage inequality between regions.